DOMESTIFIKASI IKAN BETOK Anabas testudineus MELALUI PEMIJAHAN DI WADAH BUDIDAYA - Untung Bijaksana (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The study is intended as an attempt domestication through climbing perch spawning in the container cultivation. The research was conducted at the Laboratory of Wetlands Program University Faculty of Fisheries Aquaculture Lambung Mangkurat.Three main points in support of the spawning success of fish, namely: gonadaldevelopment, ovulation and spawning. Naturally development climbing perch fishgonads occurred in the early dry season to peak season and at the beginning of the rainy season or during the rainy season, spawning occurred. This natural state is trying to be adopted in the cultivation of container, with fashting for 1, 2 and 3 days with water levels, 10, 15 and 20 cm. The result is a latent time of 11.7 hours to 39 hours, fecundity between 5310 to 7376 grains, egg diameter 0.5 to 0.8 mm, the degree of fertilization between 88.2 to 93.2 percent and the degree of hatching between 87, 0 to 91.6 percent.